The Influence Of Modified Concrete In Loftvilles City Apartment Project In South Tangerang, Banten - Olfa Finatry; Mirnayani Mirnayani; Mohamad F. N. Aulady (Faculty of Engineering, Malikussaleh University, 2018)
As one of major works in a construction project, reinforcing steel has to be carried out effectively and efficiently. Unfortunately, obstacles often occur on site, such as the massive spacer chair volume that demands higher cost and time to finish. To solve this problem, we would like to substituting the spacer chair with modified concrete construction that was first proposed by PT. PP (Persero). The result of this research proved that duration gap between those methods was 1 working day. This indicate that concrete modification is more effective than conventional spacer chair